Truth and Method - Aranjanil, G. (Journal of Dharma, 1980)
Hans-George Gadamer, Truth and Method, Translation from the second German edition (1965), .ed. Garrett Barden and John Cumming. New York: The Seabury Press, pp. xxvi + 55], $ 22/50.